PENGEMBANGAN MEDIA PEMBELAJARAN SMART SNAKE DALAM PEMBELAJARAN BAHASA ARAB - Siti Maisaroh; Amrini Shofiyani; Siti Sulaikho' (Al-Lahjah, 2020)
Abstract Arabic learning consists of 4 fields, namely listening, reading, speaking and writing. Some of the students felt that memorizing and saying vocabulary in Arabic was difficult. Therefore, researchers used smart snake learning media in learning Arabic. This study aims to determine the development and the effective use of smart snake learning media in learning Arabic in the field of reading in Madrasah Aliyah Unggulan KH. A. Wahab Hasbullah. This study uses research and development of the ADDIE (analys, design, development, implementation, and evaluation) model. Data collection is generated by observation, questionnaires, interviews, and tests. The results of the learning media validation from the material experts and the media experts showed 100%. Based on this, the media developed for qualification are very valid. The results of the experimental design conducted by researchers showed that learning by using smart snake learning media was effective. This is proven by the value of sig.(2-tailed) of the post-test in the control and experimental class is smaller than sig.0.05 which is 0,000. The conclusion of these results is Ho: "There is no significant difference between learning Arabic by using smart snake learning media or not" rejected. Therefore, Ha "There is a significant difference between learning Arabic by using smart snake learning media or not" is accepted. Keywords: Development, Media in Learning, Smart Snake, Learning Arabic